2023
DOI: 10.1111/rda.14333
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of semen quality and anti‐oxidative enzyme activity between bovine sex‐sorted and non‐sex‐sorted frozen–thawed semen

Abstract: In the current study, the difference between the sex‐sorted and non‐sex‐sorted frozen semen of Holstein Friesian breed cattle was investigated. Significant variation (p < .05) was found in the semen quality parameters such as motility; vitality; acrosome integrity rate; the anti‐oxidative enzyme activity including GSH (glutathione); SOD (superoxide dismutase); CAT (catalase); GSH‐Px (glutathione peroxidase) and the rate of fertilization. The results showed that the sperm acrosome integrity and motility of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…For instance, the commercially employed method (flow cytometry) for sorting semen kills the sperm cells during selection (27). Other studies have reported a noticeable decrease in sperm quality following sexing semen (45,46).…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…For instance, the commercially employed method (flow cytometry) for sorting semen kills the sperm cells during selection (27). Other studies have reported a noticeable decrease in sperm quality following sexing semen (45,46).…”
Section: Discussionmentioning
confidence: 93%
“…Despite the low conception rate following the use of sexed semen in goats, sheep, and cattle, the method is accurate (39,40,44). This finding, therefore, necessitates more innovation studies to come up with a sexing technology that will protect sperm cell injuries during sorting, ehich was supported by the evidence from Silva et al's (45) study in frozen-thawed goats' sperm cells and Guo et al's (46) study in frozen-thawed cattle's sperm cells. However, the type of insemination used in goats, sheep, and cattle also affects the conception rate following the use of sexed semen (12,35,37,41,59).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations